Students' Strategies and Creativity in Solving Mathematical Literacy Problems - Usman Mulbar; Ahmad Zaki; Mar Athul Wazithah T; Muhammad Farhan (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to describe students’ strategies and creativity in solving mathematical literacy problems. Mathematical literacy requires students not only to understand mathematical concepts but also to select appropriate problem-solving strategies and apply creative thinking in various contexts. Therefore, understanding how students use strategies and demonstrate creativity in solving mathematical literacy problems becomes important. The research employed a qualitative descriptive method involving junior high school students who were categorized into high, medium, and low ability levels based on the results of a mathematical literacy problem-solving test. The main instruments were the researchers themselves, while the supporting instruments included a mathematical literacy test, interview guidelines, and validation sheets. Data were collected through two stages of testing and two stages of interviews, and triangulation was employed to ensure data validity. In addition, triangulation across methods and time was employed to enhance the validity of the data. The results showed that students demonstrated different strategies and levels of creativity in solving problems. Students in the high-ability category were able to understand problems well, choose appropriate strategies, and exhibit all indicators of creativity—fluency, flexibility, and novelty. Medium-ability students showed fluency and novelty or flexibility and novelty, while low-ability students generally did not meet any creativity indicators due to difficulties in understanding the problems and selecting proper strategies.